Aplastic anemia and risk of deep vein thrombosis and pulmonary embolism: A nationwide cohort study. Issue 149 (January 2017) - Lin, Chun-Liang; Lin, Cheng-Li; Tzeng, Shu-Ling; Chung, Wei-Sheng
Abstract: Objectives: Deep vein thrombosis (DVT) and pulmonary embolism (PE) constitute venous thromboembolism (VTE), which is not fully known in aplastic anemia (AA). Therefore, we investigated the incidence and risk of VTE in AA patients. Methods: We conducted a nationwide cohort study to investigate the risk of DVT and PE in patients with AA. We identified patients with newly diagnosed AA as the AA cohort between 2000 and 2010 from the National Health Insurance Research Database (NHIRD). The initial admission date for AA diagnosis was set as the index date. For each patient with AA, 4 patients without a history of AA, frequency matched by sex, age (every 5-y span), and year of index date, were the non-AA cohort. All patients were followed from the index date to the date of DVT or PE diagnosis, withdrawal from the NHIRD, or the end of 2011. Cox models were used to evaluate the risk of developing DVT and PE in the AA cohort. Results: We included 4001 and 15, 998 patients in the AA and non-AA cohorts, respectively, and the overall incidence densities of VTE were significantly higher in the AA cohort than in the non-AA cohort (42.3 vs 10.2 per 10, 000 person-years). The AA cohort had a 2.56-fold higher risk of VTE (95% confidence interval [CI] = 1.81–3.63) than did the non-AA cohort. Conclusion: This nationwide cohort study indicated that AA is associated with increased incidence and risk of VTE. Highlights: The overall incidence densities of venous thromboembolism (VTE) were significantly higher in the aplastic anemia (AA) cohort than in the non-AA cohort (42.3 vs 10.2 per 10 000 person-y). The AA cohort had a 2.56-fold higher risk of VTE than did the non-AA cohort. A substantially high risk of DVT was observed within the first 0.5 years of AA diagnosis.